Mitigating Village Fund Fraud in Indonesia: The Role of Leadership, Transparency, and Community Engagement – Study in Central Bengkulu Regency - Indah Oktari Wijayanti; Herawansyah Herawansyah; Danang Adi Putra; Budi Utomo (Open Access Indonesia Journal of Social Sciences, 2024)
Village fund management in Indonesia is crucial for rural development and poverty reduction. However, it is susceptible to fraud, hindering progress and eroding public trust. This study investigates the influence of leadership commitment, external supervision, reporting transparency, and community participation on fraud prevention in village fund management in Central Bengkulu Regency. A quantitative approach was employed, utilizing a survey method with 102 respondents, including village officials, government auditors, and related stakeholders. Data analysis was conducted using multiple linear regression to examine the relationship between the independent variables (leadership commitment, external supervision, reporting transparency, and community participation) and the dependent variable (fraud prevention). The findings demonstrate that leadership commitment, external supervision, reporting transparency, and community participation have a significant positive effect on fraud prevention in village fund management. Leadership commitment fosters an accountable organizational culture, while external supervision strengthens control mechanisms. Reporting transparency enhances public scrutiny, and community participation creates effective social control to minimize potential budget irregularities. In conclusion, This study recommends strengthening human resource capacity through training and education, increasing technology-based transparency for better information access, and promoting wider community involvement in the planning, implementation, and supervision of village funds. These measures collectively contribute to a more robust and fraud-resistant village fund management system.